Expanding learning in clergy leadership formation in an Anglican Church Province in Southern Africa: a critical realist study - Chinganga, Percy (Rhodes University, Faculty of Education, Department of Education, 2019)
The focus of this study was to investigate the kind of learning that happened when participants involved in clergy leadership formation programmes and activities in the Anglican Church of Southern Africa (ACSA) engaged in their responsibilities as a collective. Further, the research sought to explore collaborative and transforming practices in ACSA clergy leadership formation programmes and activities which could be expanded through learning. The study is premised on an investigation of the historical foundations of Christian leadership formation processes which sought to establish clergy leadership formation models relevant to ACSA (the context of the study) from inception (1848) to date (2017). This entailed investigating how the developments which have happened in the church from its inception in the New Testament times through the Medieval and Reformation periods, have contributed to the emergence of distinct Christian leadership formation models which have formed the basis of clergy leadership formation in ACSA. Accordingly, the study highlighted key issues relating to clergy leadership formation which are discernible in the different historical phases of the life and work of the church with the objective of establishing how ACSA, through expansive learning, could transform her current clergy leadership formation model(s) towards collaborative and transforming practices. The concept of expansive learning, drawn from Cultural Historical Activity Theory (CHAT), was used in the study as a methodological tool to create an environment where research participants (formators) from several dioceses would engage in collective work activities which would surface contradictions relating to how clergy leadership formation programmes and activities were understood and facilitated in ACSA. In response to the surfaced contradictions, the study engaged research participants in Change Laboratory Workshops whose goal was to transform the organisation (ACSA) in two particular ways: empowerment of participants (formators) with conceptual tools relevant to their responsibilities in clergy leadership formation programmes and activities in ACSA, and improvement of organisational cultural practices, that is, the manner in which ACSA ought to conceptualise, design, plan, facilitate and manage clergy leadership formation programmes and activities. The latter brought into the discourse the need for participants (formators) to select and employ methodologies, methods, approaches and resources relevant to the southern African context where ACSA is located even though the study also acknowledged the influence of other Anglican Church contexts on what happened at the local level. In order to decipher meaning out of investigated phenomena about clergy leadership formation in ACSA, the study employed the critical realist "underlabouring" philosophy advanced by theorists such as Bhaskar to surface underlying mechanisms that exist at the level of the "real" in order to understand the causes of particular events and experiences as they manifest in the "actual" and "empirical" domains of the world, ACSA in the case of the study. In particular, the study engaged critically the opinion deliberated by critical realists concerning the interplay between structure and agency in relation to the responsibilities of the research participants (formators) in ACSA clergy leadership formation programmes and activities. For instance, the study had an interest in investigating why bishops (principal formators in ACSA) exercised their episcopal authority in the manner they do and why individual formators were concerned about particular issues which relate to the facilitation of clergy leadership formation in ACSA (agential reflexivity/subjectivity). The study observed that, in the case of diocesan bishops, critical realists would argue that, by virtue of the authority which comes with their responsibilities (agency), they have the power to influence transformation of practices in clergy leadership formation in ACSA at any given point in time. The flip side of the discourse was also taken note of: that some bishops, for reasons known to themselves and their predecessors, are often reluctant to embrace new ideas relating to clergy leadership formation practices in their dioceses. Further, through critical realist lens, the study concluded that Canons, Vision and Mission statements, Acts, and structures such as Synod of Bishops, Provincial Synod, ABoTE, Cott, and TfM structurally shape ACSA, thus providing the organisation with a stable ontology which ought to direct, regulate and control the manner in which clergy leadership formation programmes and activities were conceptualised, designed, planned, facilitated and managed. As such, the study had an interest in establishing what would happen, in relation to clergy leadership formation practices in ACSA, when these structures would have been activated? Beyond that, in view of the goal of the study, it was enquired how expansive learning processes could be helpful in responding to the research findings towards exploring collaborative and transforming clergy leadership formation practices in ACSA. Drawing from the conceptual framework which was carved in the study on the basis of the theoretical tools (critical realism and educational leadership theory) and methodological tools (CHAT orientated concepts) undergirded by the Vygotskian theorisation of human consciousness development, the study concluded that clergy leadership formation is a collaborative activity which calls for the recognition, appreciation and utilisation of available expertise in ACSA and provision of a platform where participants (formators) could engage collectively on issues relating to their work with the objective of building each other up in knowledge and skills (expansive learning) towards realisation of the goals and objectives of the organisation. Diverse understandings (contradictions) of what needed to be prioritised in the facilitation of clergy leadership formation in ACSA would be considered as a positive rather than a negative. Ultimately, through the use of inductive, abductive and retroductive modes of inference, the study modelled a transforming, transformational, transformative, embodied and incarnational model of clergy leadership formation which ACSA could consider using in future deliberations on the object of study particularly in relation to the key research findings across the case studies which were used in the study.
Keywords: Leadership -- Africa, Southern -- Religious aspects -- Christianity; Church management -- Africa, Southern; Critical realism; Educational leadership; Anglican Church of Southern Africa